2005
DOI: 10.1111/j.1471-8286.2005.00938.x
|View full text |Cite
|
Sign up to set email alerts
|

Novel polymorphic nuclear microsatellites in Cupressus sempervirens L.

Abstract: We report the characterization and optimization of nine polymorphic nuclear microsatellites from Cupressus sempervirens L. using an enriched library method. A total of 24 individuals from four different populations were used to estimate genetic diversity parameters. High level of allelic diversity was found with a number of alleles ranging from two to 13. These markers will prove very useful in screening diversity at different geographical scales and in monitoring gene flow in cypress orchards.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
13
0
1

Year Published

2009
2009
2020
2020

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 6 publications
1
13
0
1
Order By: Relevance
“…Genetic diversity in French cypress populations is similar to that in Italian populations. The null allele frequencies estimated in this study for French populations are of the same magnitude as those found by Sebastiani et al (2005) (from 0.06 to 0.19 for loci Cyp52, Cyp139, Cyp258 and Cyp293).…”
Section: Ssr Allele Diversitysupporting
confidence: 66%
See 4 more Smart Citations
“…Genetic diversity in French cypress populations is similar to that in Italian populations. The null allele frequencies estimated in this study for French populations are of the same magnitude as those found by Sebastiani et al (2005) (from 0.06 to 0.19 for loci Cyp52, Cyp139, Cyp258 and Cyp293).…”
Section: Ssr Allele Diversitysupporting
confidence: 66%
“…Inheritance of the SSR markers The analysis of allele segregations among the 77 C. sempervirens progeny produced by controlled crosses of C. sempervirens parents confirmed the putative Mendelian inheritance of the SSR markers developed by Sebastiani et al (2005).…”
Section: Discussionmentioning
confidence: 90%
See 3 more Smart Citations